2006
DOI: 10.1016/j.jcrs.2006.01.100
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsule opacification after cataract surgery in patients with diabetes mellitus

Abstract: Diabetic patients had significantly more severe PCO after cataract surgery than nondiabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 13 publications
1
39
0
3
Order By: Relevance
“…[16][17][18] But the higher incidence of PCO and surface changes could not be explained in hypertensive patients. 19 Several studies showed that IOLs have an important role in capsular opacification and capsular fibrosis, after extracapsular cataract extraction and PCIOL implantation. Anterior capsular opacification (ACO) usually occurs where capsule comes in contact with the IOL after in-the-bag implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] But the higher incidence of PCO and surface changes could not be explained in hypertensive patients. 19 Several studies showed that IOLs have an important role in capsular opacification and capsular fibrosis, after extracapsular cataract extraction and PCIOL implantation. Anterior capsular opacification (ACO) usually occurs where capsule comes in contact with the IOL after in-the-bag implantation.…”
Section: Discussionmentioning
confidence: 99%
“…To properly judge the potential of a new IOLs or a surgical method to prevent PCO, a long-term followup (usually 3 years or longer) of the included eyes is necessary 27 . We observed the PCO at 1-year intervals up to 8 years after cataract surgery; therefore the PCO change over longer period of time was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 PCO is also a frequent and important complication noticed in diabetics undergoing cataract surgery. [3][4][5][6][7][8][9] It has the potential to obscure fundus view, thereby compromising the observation and timely treatment of posterior segment pathologies such as diabetic retinopathy (DR) and macular edema.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] However, some studies have reported contradictory results regarding the prevalence of PCO in diabetic vs non-diabetic patients. [3][4][5][6] A few studies have quantitatively evaluated PCO; the results, however, are still controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation